Proposal for Training Primary School Teachers in Welcoming and Integrating Refugee Students - Reviriego Reinaldo, Noemí (2020)
The inclusion of vulnerable groups in our society, namely, at schools, has garnered special attention in recent years. As a result, a proposal to train faculty in welcoming and providing refugee children with psycho-pedagogical support is, hereby, presented. The goal is to promote the acquisition and development of emotional education tools and resources among teachers for this purpose. Data for proposed training plan was obtained from a survey completed by 27 teachers from various schools throughout Spain. The survey was used to gain insight into teachers´ knowledge about the needs and social-emotional education of refugee students. The objectives of the training plan include understanding the struggle of refugee students, training in welcoming them and provide emotional support throughout their integration and settlement process.  To achieve these objectives teachers will receive training in practical actions and activities during nine three-hour workshops. The training proposal was reviewed by an expert on refugees who also provided recommendations.